Organizational model of commercialization and technology transfer - Reichling, Peter; Veres Somosi, Mariann; Kobielieva, Tetiana (ФОП Томенко Ю. І., 2020)
It is proved that the commercialization of innovations involves the creation of a special modeling system for managing innovation processes and activities on the basis of creative management decisions, which would take into account the peculiarities of their functioning and patterns of development in business.
Keywords: commercialization; transfer; technology; development; innovation; enterprise